BANDITRY AND CRISIS OF PUBLIC SAFETY IN NIGERIA: ISSUES IN NATIONAL SECURITY STRATEGICS - Al Chukwuma, Okoli; Francis, Okpaleke (European Scientific Journal, ESJ, 2014)
This paper examines the phenomenon of banditry in relation to contemporary crisis of public safety in Nigeria. Relying on exegesis of relevant secondary sources, the paper posits that banditry constitutes a serious threat to Nigeria’s public safety and, by extension, national security. The paper recommends, among other things, a Public-Private-Partnership (PPP) approach to policing as a means of addressing the rising prevalence of banditry in Nigeria.